Altered atrial restitution dynamics and refractoriness in metabolic syndrome due to up-regulation of potassium repolarizing currents increases susceptibility to atrial fibrillation. (14th October 2021) - Calvo, C J; Rodriguez, A; Almar, E; Arias, O; Lozano, W; Alberola, A; Zarzoso, M
Abstract: Background: Metabolic alterations, such as Metabolic Syndrome (MS), describe an association of factors including diabetes, hypertension, obesity and dyslipidemia, linked to higher risk and prevalence of overall cardiovascular disease, arrhythmogenesis and sudden cardiac death. Obese and diabetic patients have shown an increased risk for developing atrial fibrillation (AF). However, underlying mechanisms are not understood. Purpose: To study the effects of MS and obesity remodeling in atrial restitution dynamics, frequency-dependent adaptation, refractoriness and its potential susceptibility to AF. Methods: Electrophysiological experimental data from High-fat (HF-O, standard rabbit chow with an additional 15% fat) and Hig-fat High-Sucrose Metabolic Syndrome (HFHS-MS, 10% hydrogenated coconut oil and 5% lard, 15% high-sucrose dissolved in water) rabbit models were used to adjust computational models atrial electrophysiology remodeling under each condition. Additionally, isoproterenol and AF conditions were considered to challenge both in-silico models. Validation and sensitivity analysis were performed for each model parameters. Computational simulations in conditions of pacing at different pacing cycle lengths was assessed at 100, 125, 150, 200, 250, 350, 450, 500, 650, 750, 850, 1000 ms. Restitution dynamics were automatically determined and analyzed, as well as restitution slopes and presence of automaticity, early after-depolarizations, alternans and cardiac arrhythmia induction. Results: Shortening of action potential duration and refractoriness in the left atrium was observed under HFHS-MS. Upstroke velocity, maximum excitability and sodium availability were altered both in HF-O and HFHS-MS. HF-O remodeling showed presence of alternans at high pacing frequencies. Repolarization restitution was shortened in conditions of ISO and MS-AF. Restitution slopes were >1 in HF-O and HFHS-MS, which was correlated to higher susceptibility to AF, and further increased in MS-AF. Under MS-AF, abbreviation in APD in both atria, resulted in increased reentrant frequencies in AF, which was exacerbated under IK1 up-regulation, increasing atrial vulnerability. Conclusions: HFHS-MS underlies modifications in atrial electrophysiology including shorter refractoriness in HFHS-MS, as well as modifications in atrial excitability, which may be pro-arrhythmic mainly at high frequency rates. This could be explained in part by an up-regulation of outward potassium channels. These results could partially explain increased susceptibility for AF in MS. Funding Acknowledgement: Type of funding sources: None.